Brainstem auditory evoked potentials features in thalassemia major - Jimmy Passat; Bulan Ginting Munthe; Fauzi Mahfuzh; Taralan Tambunan (Paediatrica Indonesiana, 2001)
Patients with thalassemia major are at high risk for hearing impairment. The objective of the study is to determine the prevalence, grade and type of hearing impairment according to brainstem auditory evoked potentials (BAEP) investigation in thalassemia major. A descriptive cross sectional study was conducted between December 1999 until August 2000 in 72 thalassemic patients between 3 and 18 years of age. Only 65 patients were evaluated, because of time limitation. The results showed the prevalence of hearing impairment in thalassemia major was 29.2%. Most of them were moderate to severe unilateral sensorineural hearing impairments. Mild sensorienural hearing impairment occured in only 12.3%. Conductive  hearing impairment was only found in 1 patient. Hearing impairment was frequently found between 7 to 12 years of age (41.5%). Conclusion: the prevalence of hearing impairment in thalassem a major according to BAEP investigation is high and BAEP examination should be done regularly in all of thalassemic patients to investigate early detection and treatment of hearing impairment.